Δ*-Lindelof tritopological spaces. Issue 5 (4th July 2022) - Mousa, Zainab Imran; Habeeb, Eman Yahea; Hassan, Asmhan Flieh
Abstract: In this work, we introduce and study the Lindelof tritopological spaces w.r.t. δ *-open set (which we named δ *-Lindelof tritopological spaces) and investigate some of their characterizations. And we also show the main interrelations between δ *-Lindelofness and various basic notions of tritopological spaces, such as, δ *-compactness, δ *-separability, δ *-second countability, and others. Furthermore, we also show that the property of a δ *-Lindelofness is not a hereditary property, however it is a tritopological property.